Conserving Urban Wildlife in the Face of Climate Change - Daniel Feinberg; Mark Hostetler (EDIS)
Virtually all climatologists agree that humans are increasing the rate of the Earth’s warming by releasing greenhouse gases into the atmosphere. But you might be surprised to learn that houses and residential neighborhoods are sources greenhouse gases of carbon because everything in a house that runs on electricity or gas is often derived from burning fossil fuels. This 4-page fact sheet describes the connections between climate change, wildlife, and human neighborhoods and presents several ways for residents to live more sustainably. Written by Daniel Feinberg and Mark Hostetler and published by the UF Department of Wildlife Ecology and Conservation, September 2013.